A case study of hospital contraceptive waste management practices in Chukwuemeka Odumegwu Ojukwu University Teaching Hospital, Awka, Anambra State - Tyotswam, Yanmeer S.; Iseme, Rosebella A.; Makunyi, Eliphas G. (International Journal Of Community Medicine And Public Health, 2024)
Background: Effective management of hospital waste is a critical component of a hospital’s infection control program and is central to occupational safety for healthcare workers. Thus, this study focused on the assessment of hospital contraceptive waste management practices at Chukwuemeka Odumegwu Ojukwu University Teaching Hospital (COOUTH) Awka, Anambra state, Nigeria. Methods: A cross sectional analytical study was carried out among healthcare workers selected using multistage sampling technique in 6 categories of healthcare workers in COOUTH. Data was collected using a pre-tested semi-structured interviewer-administered questionnaire and a World Health Organization (WHO) checklist and analyzed using statistical package for the social sciences (SPSS) version 22. Associations and correlations between variables were tested at the bivariate level using Chi-square and t-test. Results: A total of 86 healthcare workers were surveyed. The majority of the respondents were females, nurses with RN qualification. The mean knowledge score of the respondents was 94.8%. The attitude of healthcare workers towards segregation of hospital contraceptive waste at source point was 71% while the usage of gloves in handling hospital waste was 95.3%. The major factor affecting contraceptive waste management practices in the facility was the respondent’s cultural beliefs. The lack of funds to finance standard waste disposal methods was noted to be a significant barrier to optimum waste management practices. Conclusions: This study showed that despite the high level of knowledge of healthcare workers on hospital contraceptive waste management practice in COOUTH, the hospital contraceptive waste management practice is not functioning optimally in Anambra state. Hence, the need to reform the hospital waste management practice to achieve functional results.